A markerless motion capture system can reliably determine peak trunk flexion while squatting with and without a weighted vest. (May 2023) - Andersen, J.T.; McCarthy, A.M.; Wills, J.A.; Fuller, J.T.; Lenton, G.K.; Doyle, T.L.A.
Abstract: Markerless motion capture has improved physical screening efficiency in sport and occupational settings; however, reliability of kinematic measurements from commercial systems must be established. Further, the impact of torso-borne equipment on these measurements is unclear. The purpose of this study was to evaluate the reliability of HumanTrak, a markerless motion capture system, for estimating peak trunk flexion in squat movements with and without a weighted vest. Eighteen participants completed body weight squats (BWSQ) and overhead squats (OHSQ) to their maximum depth (unrestricted-range) and to a plyometric box (fixed-range) while wearing no body armour (NBA) or 9 kg body armour (BA9). Peak trunk flexion was measured using HumanTrak. Testing was performed in two sessions on one day (intra-day) and one session on a separate day (inter-day) to assess reliability. HumanTrak had a standard error of measurement < 3.74° across all movements and conditions. Reliability was good to excellent (ICC = 0.82–0.96) with very large to nearly perfect Pearson correlations ( r > 0.80) for all comparisons except unrestricted-range BWSQ with BA9 (ICC = 0.60–0.71, r = 0.71). HumanTrak was more reliable for intra- than inter-day, but reliability was still excellent for almost all inter-day comparisons (ICC > 0.82). HumanTrak is reliable for detecting differences in peak trunk flexion > 8.5° when body armour is not worn and > 10.5° when body armour is worn. Practitioners can assess meaningful changes in sagittal plane trunk motion when screening squat movements regardless of whether body armour is worn.